Understanding care in the feeding of family members/caregivers of elderly people with Alzheimer's disease (Research, Society and Development, 2020)
The objective of this study was to understand the understanding of family members/caregivers of elderly people with Alzheimer's disease about nutrition in preventing the disease. This is an exploratory, descriptive research with a qualitative approach, developed with seven family members/caregivers of elderly people with Alzheimer's disease, participants in a support group for family members/caregivers of people with Alzheimer's disease, located in a city of Rio Grande do Sul, Brazil. Data were collected in the period from April to May 2017, using the Focus Group technique, and were analyzed using the content analysis technique. As a result, six categories were identified: Food as a Health enhancer; food as a feeling enhancer; food as a way to bring people together; relationship between food and Alzheimer's disease; stimuli in the diet of the elderly person; food as a memory enhancer. It is concluded that family members/caregivers recognize the importance of food in the daily life of the elderly with Alzheimer's disease.